2022
DOI: 10.35449/jemasi.v18i2.545
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Mj Enamel

Abstract: The purpose of this study is to test and analyze the effect of Price, Product Quality and Service Quality on Customer Satisfaction. The sampling method uses Accidental Sampling. The number of samples used in this study are 60 customer respondents from MJ ENAMEL. Then an analysis of the data obtained by using quantitative data analysis. Quantitative data analysis assisted by the SPSS 21 Application program includes; validity and reliability test, normality test, multiple regression analysis, coefficient of dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
2
1
0
2
Order By: Relevance
“…The better the comfort consumers feel, the higher their sense of satisfaction. Researchers found that service quality positively and significantly affected consumer satisfaction (Mahira et al, 2021). The same results were found in research (Nanincova, 2019) ; (Agustin et al, 2021) ; (Ismail & Yusuf, 2021); and (Indriati & Fitriana, 2022).…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…The better the comfort consumers feel, the higher their sense of satisfaction. Researchers found that service quality positively and significantly affected consumer satisfaction (Mahira et al, 2021). The same results were found in research (Nanincova, 2019) ; (Agustin et al, 2021) ; (Ismail & Yusuf, 2021); and (Indriati & Fitriana, 2022).…”
Section: Introductionsupporting
confidence: 66%
“…Research states that service quality positively and significantly influences consumer satisfaction (Novitawati & Prihatminingtyas, 2019). The same results were found in research (Mahira et al, 2021); (Nanincova, 2019); (Agustin et al, 2021); (Ismail & Yusuf, 2021); (Indriati & Fitriana, 2022). With the results of this research having a significant positive effect, this research is in line with previous research.…”
Section: The Influence Of Service Quality On Customer Satisfactionsupporting
confidence: 61%
“…Sudimin mengartikan loyalitas sebagai komitmen pegawai untuk mencurahkan seluruh waktu, tenaga, dan bakatnya untuk mencapai tujuan organisasi. (Zakaria, 2019). Selain merespons secara dinamis, Anda harus selalu menerapkan konsepkonsep unggul, meninggalkan kebiasaan buruk, dan terus berinovasi dalam hal pemasaran di suatu perusahaan (Winanda Ayu Risma Maulida, 2023).…”
Section: Loyalitas Konsumenunclassified
“…Adapun beberapa penelitian terdahulu yang menjelaskan bahwa variabel X berpengaruh signifikan terhadap fariabel Y, diantaranya : Agustin, et al (2021), Saripudin, et al (2021), Mahira, et al (2021), Gofur, (2019), Sumual, et al (2021, Simon, at al (2016)…”
Section: Kerangka Penelitianunclassified